2017
DOI: 10.1007/s10654-017-0299-y
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal outcomes following exposure in utero to fallout from Chernobyl

Abstract: Iodine 131 (I-131), the principal component of nuclear fallout from the Chernobyl accident, concentrates in the thyroid gland and may pose risks to fetal development. To evaluate this, neonatal outcomes following the accident in April of 1986 were investigated in a cohort of 2582 in utero-exposed individuals from northern Ukraine for whom estimates of fetal thyroid I-131 dose were available. We carried out a retrospective review of cohort members' prenatal, delivery and newborn records. The relationships of do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 39 publications
0
16
0
2
Order By: Relevance
“…This analysis showed a dose-dependent reduction in head and chest circumference with a fetal dose dependent increase in gestational length (0.5 weeks/Gy) but not an increase in birth weight. They concluded that the observed effects were consistent with radiation effects among utero-exposed infants of Japanese atomic bomb survivors [40]. A team led by Prof. Eugenia Stepanova in Kiev examined the health outcomes of intra-uterine irradiation associated with Chernobyl exposure among mothers with acute and chronic exposure and compared them with a control group of children presumably non-exposed.…”
Section: A Review Of Reproductive Outcomes Among Chernobyl-exposed Pomentioning
confidence: 73%
“…This analysis showed a dose-dependent reduction in head and chest circumference with a fetal dose dependent increase in gestational length (0.5 weeks/Gy) but not an increase in birth weight. They concluded that the observed effects were consistent with radiation effects among utero-exposed infants of Japanese atomic bomb survivors [40]. A team led by Prof. Eugenia Stepanova in Kiev examined the health outcomes of intra-uterine irradiation associated with Chernobyl exposure among mothers with acute and chronic exposure and compared them with a control group of children presumably non-exposed.…”
Section: A Review Of Reproductive Outcomes Among Chernobyl-exposed Pomentioning
confidence: 73%
“…Therefore, it is of no surprise that no unequivocal evidence has been obtained yet. For example, in a study mentioned in the introduction [31], there was no statistically signi cant effect (pvalue > 0.1) of fetal dose on birth weight in 2,582 in utero-exposed individuals from northern Ukraine for whom estimates of fetal thyroid I-131 dose were available. Because of this relatively small population size (n=2,582), the statistical power for detecting a relevant 10% increase in LBW prevalence, which prevalence is itself in the range of 10%, achieves only 40%.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, it is of no surprise that no unequivocal evidence has been obtained yet. For example, in a study mentioned in the introduction [31], there was no statistically signi cant effect (p-value > 0.1) of fetal dose on birth weight in 2,582 in-utero-exposed individuals from northern Ukraine for whom estimates of fetal thyroid I-131 dose were available. Because of this relatively small population size (n=2,582), the statistical power for detecting a relevant 10% increase in LBW prevalence, which prevalence is itself in the range of 10%, achieves only 40%.…”
Section: Discussionmentioning
confidence: 94%